Computers and productivity: are aggregation effects important? - McGuckin, Robert H.; Stiroh, Kevin J. (Economic Inquiry, 2002)
This article examines the empirical implications of aggregation bias when measuring the productive impact of computers. To isolate “aggregation in variables” and “aggregation in relations” problems, we compare production function estimates across specifications, econometric estimators, and data levels. The results show both sources of bias are important, especially when moving from sectors to the economy level, and when the elasticity of all types of noncomputer capital are restricted to be equal. The elasticity of computers is surprisingly stable between industry and sector regressions and does not appear biased by incorporating a restrictive measure of noncomputer capital. The data consistently show that computers have a large impact on output. Reprinted by permission of the publisher.